Prevalence of overweight, obesity, and early adiposity rebound in nursery school children in southeastern France - Roth, B.; Reynaud, R.; Nègre, V.; Gentile, S.; Pauly, V.; Bernard, O. (Archives de pédiatrie : organe officiel de la Société française de pédiatrie, 2022)
The aim of the present study was to assess the prevalence of overweight, obesity, and early adiposity rebound in nursery school children aged 3.5–4.5 years and to evaluate associations with deprivation. A cross-sectional study was conducted in the Bouches-du-Rhône department in southeastern France. Data for all nursery school children aged 3.5–4.5 years were collected during systematic medical examinations. The prevalence of overweight and obesity was determined using French, International Obesity Task Force (IOTF), and World Health Organization reference values. A French ecological deprivation index was used to assess associations with deprivation. Among 19,295 children included in the study, the prevalence of overweight (IOTF-25 < BMI < IOTF-30) was 9.1% and the prevalence of obesity (BMI > IOTF-30) was 2.6%. Children attending nursery schools in the most disadvantaged areas were 4.3 times more likely to be affected by obesity than those from schools in the most advantaged areas (OR: 4.32; 95% CI: 2.98–6.25, p < 0.001), after adjusting for gender, age group, and school status. Early adiposity rebound was observed in 2131 of 9872 children (21.6%). Programs to prevent childhood overweight and obesity in France should be intensified and take account of major persistent social inequalities. Medical practitioners should learn to systematically assess BMI curve dynamics and early adiposity rebound.